Pengurusan Warisan Atas Onbeheerde Nalatenschap Oleh Lembaga Balai Harta Peninggalan Bersama Notaris/PPAT - Widyantara Putra, I Ketut; Satyayudha Dananjaya, Nyoman (Kertha Patrika; Vol 46 No 1 (2024)DO - 10.24843/KP.2024.v46.i01.p05, 2024)
The process of inheritance that is not managed (onbeheerde nalatenschap) is the aim of this research until finally the inheritance passes to the state, as well as knowing the position of the state and the role of the state and the Notary/PPAT in managing the inheritance that is not managed. Normative research is used as the research method, when typing in inheritance, no one appears as an heir so it is classified as neglected inheritance (Onbeheerde Nalatenschap). The Heritage Hall is one of the state's efforts to realize aspects of the use and maintenance of any inherited assets that are not managed and to create orderly administration. The Inheritance Property Hall in the form of efforts to maintain and care for inherited assets that are not managed in order to maintain the value of the assets under the care of the Inheritance Hall, is expressed in 2 ways, namely through a rental process through making a rental agreement before a Notary, and carry out buying and selling before the PPAT by obtaining a sales permit from the Ministry of Law and Human Rights. Proses dari pewarisan yang tidak terurus (onbeheerde nalatenschap) merupakan tujuan penelitian ini hingga akhirnya warisan tersebut jatih kepada negara, serta mengetahui kedudukan negara dan peran negara serta Notaris/PPAT dalam mengurus harta warisan yang tidak terurus tersebut. Penelitian normatif digunakan sebagai metode penelitian ini, ketikan dalam pewarisan tidak ada satupun yang yang muncul sebagai seorang ahli waris sehingga sebagai harta peninggalan tak terurus (Onbeheerde Nalatenschap). BHP dalam upaya menjaga nilai dari harta peniggalan yang tidak diurus tersebut dalam upaya pemanfaatan yang dapat dilakukan dengan sewa menyewa ataupun jual beli melalui akta yang dibuat oleh Notaris/PPAT agar menjaga nilai dari suatu harta peninggalan yang tidak diurus tersebut sehingga tidak mengalami pengurangan nilai atau hilangnya nilai.